Substrate specificity of FUT8 and chemoenzymatic synthesis of core-fucosylated asymmetric N-glycans. Issue 17 (15th April 2016) - Calderon, Angie D.; Liu, Yunpeng; Li, Xu; Wang, Xuan; Chen, Xi; Li, Lei; Wang, Peng G.
Abstract : Based on substrate specificity of human FUT8, an efficient strategy was developed for the synthesis of core-fucosylated asymmetric N -glycans. Abstract : Substrate specificity studies of human FUT8 using 77 structurally-defined N -glycans as acceptors showed a strict requirement towards the α1, 3-mannose branch, but a great promiscuity towards the α1, 6-mannose branch. Accordingly, a chemoenzymatic strategy was developed for the efficient synthesis of core-fucosylated asymmetric N -glycans.